Adiabatic kinetics of phase transformation in shape memory TiNi alloy subjected to shock loading. Issue 18 (17th September 2021) - Liu, Yonggui; Hui, Mengmeng; Shen, Lingyan
ABSTRACT: In this paper, we study the adiabatic kinetics of martensitic phase transition induced by shock loading. Our main goals are to reveal the effect of thermal–mechanical coupling on phase interface propagation by demonstrating the wave profiles to the impact loading. First, a kinetics and constitutive model for shape memory TiNi alloy with thermo-mechanical coupling effect was preliminarily established based on the laws of thermodynamics. Then the numerical results show that phase transformation shock waves during shock loading and unloading would be aroused due to the nonlinear hardening since adiabatic temperature rise. The shock front and the temperature interface were coupled to each other. Moreover, the adiabatic temperature rise across the transformation shock front effectively reduces the driving force of phase transition and increases the propagation velocity of phase transition wave. Finally, the theoretical results are compared with the experimental results. The comparison results reflect the intrinsic thermo-mechanical coupling characteristic of shape memory TiNi alloy with strong nonlinear constitutive behaviour and kinetics, which will be helpful for temperature controlling for TiNi alloy material and structures subjected to blast or impact loading.